Word to the wise - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries., 2019)
"It's no-holds-barred murder, in the latest page-turning Library Lover's Mystery. Lindsey Norris is finally getting married to the man of her dreams--but it's not all roses for Briar Creek's beloved library director, as gardening enthusiast and town newcomer Aaron Grady gives the term "book lover" a whole new meaning. Inappropriate looks and unwelcome late-night visits to Lindsey's house have everyone from the crafternooners to Lindsey's fiancé, Sully, on edge. When Grady's dead body is found staged outside the library and all the clues point to Sully, Lindsey knows it's up to her to dig through the hidden chapters of Grady's previous life to find the real culprit and clear Sully's name. But becoming a thorn in the killer's side is not without its consequences, and the closer Lindsey gets to the truth, the more determined the murderer is to make her just a footnote"--